Gender Barriers in Higher Education: The Case of Taiwan - Wang, Ru-jer (Education Policy Analysis Archives, 2001)
As a consequence of the rapid expansion of higher education in Taiwan over the past decades, the enrolment of females in higher education has grown considerably. However, this article reports that in terms of institutional difference, access to advanced study, and differing subject preferences, the barriers to women's participation in higher education remain. Thus, the findings drawn from this article lead to the conclusion that females still suffer disadvantages in access to higher education, although the expansion of higher education in Taiwan has substantially benefited females over the past few decades.